An analytical perspective on enhancing activity document management quality in the digital age through ISO 15489 - CHEMAA, Souheir; BOUKERZAZA, Kamel (Journal of Human Sciences, 2025)
Enhancing activity document management has become imperative in complicated evolving digital contexts. Thus, organizations must integrate digital technology with administrative rules to ensure business continuity and create information management systems that help them achieve their objectives. Therefore, as a primary reference in the field of record management, this article discusses the importance of applying ISO 15489 to enhance document management quality in the current digital age by explaining the goals, principles, and significance of this standard in controlling digital information flow, along with ensuring document authenticity and an integrated digital work environment, plus well-informed decisions based on trustworthy data, and providing a framework that assists in creating efficient record management policies and systems.